Hydrogen relative permeability modeling: applications to underground hydrogen storage (UHS) - Agbamu, Deborah Olabisi (My University, 2025)
The transition toward a low-carbon energy system has intensified interest in underground hydrogen storage (UHS) as a means to balance the intermittent nature of renewable energy sources. The accurate modeling of hydrogen flow in subsurface porous media is crucial for optimizing storage efficiency and ensuring successful retrieval. A key parameter in this process is hydrogen relative permeability (k_rh), which governs multiphase flow dynamics in geological formations. In this study, we develop a theoretical model for k_rh using the effective-medium approximation (EMA) and percolation theory (PT) concepts. Our model incorporates pore-scale characteristics such as pore size distribution, connectivity, and critical hydrogen saturation S_hc. The model is validated against eight experimental datasets and eleven pore-network simulations, demonstrating reasonable agreement in most cases. However, discrepancies are observed in certain carbonate samples, likely due to secondary porosity effects (e.g., vugs and fractures) and in sandstones with possible microfractures. The findings highlight the critical role of accurately estimating S_hc in predicting k_rh and suggest that improvements in pore structure characterization could enhance modeling accuracy.
Keywords: Effective-medium approximation; Percolation theory; Capillary pressure; Hydrogen relative permeability; Underground hydrogen storage